A guide to SDG interactions: From science to implementation - Nilsson, M.; Griggs, D.; McCollum, D.; Stevance, A (International Science Council, 2017)
The United Nations’ 2030 Agenda for Sustainable Development was adopted in September 2015. It is underpinned by 17 Sustainable Development Goals (SDGs) and 169 targets. National policy-makers now face the challenge of implementing this indivisible agenda and achieving progress across the economic, social and environmental dimensions of sustainable development world-wide. As the process moves towards implementation, there is a need to address the scope and systemic nature of the 2030 Agenda and the urgency of the challenges. This requires a wide range of tools and science-based analysis to navigate that complexity and to realise the ambition. This report explores the nature of interlinkages between the SDGs. It is based on the premise that a science-informed analysis of interactions across SDG domains – which is currently lacking – can support more coherent and effective decision-making, and better facilitate follow-up and monitoring of progress. Under standing possible trade-offs as well as synergistic relations between the different SDGs is crucial for achieving long-lasting sustainable development outcomes. A key objective of the scoring approach described here is to stimulate more science-policy dialogue on the importance of interactions, to provide a starting point for policy-makers and other stakeholders to set their priorities and implementation strategies, and to engage the policy community in further knowledge developments in this field.